2023
DOI: 10.3390/beverages9020051
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Fermented Beverages Processing: The Use of Emerging Technologies

Mariana Morales-de la Peña,
Graciela A. Miranda-Mejía,
Olga Martín-Belloso

Abstract: Since ancient times, fermentation has been one of the most utilized techniques for food preservation and for the development of natural products with functional properties at low cost. Nowadays, fermented foods and beverages are highly attractive to consumers since they are perceived as natural and potential sources of functional compounds. Research efforts conducted in this area over the years have allowed for an understanding of the main reactions occurring during fermentation related to microbial growth, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Pasteurization and UHT processes are the most used in the dairy industry; however, studies have suggested the application of emerging technologies, such as ohmic heating (OH), moderate electric fields (MEF), pulsed electric fields (PEF), ultrasound (US), and high hydrostatic pressures (HHP). Most of these processes are non-thermal and could in addition, reduce fermentation time, guarantee or increase the viability of the probiotic, and improve taste and nutritionalquality properties, in addition to increasing shelf life [120]. Subsequently, the milk is cooled (to around 42 to 45 • C) so that starter and probiotic cultures can be added.…”
Section: Aspects Related To the Fermentation Of Probiotic Functional ...mentioning
confidence: 99%
“…Pasteurization and UHT processes are the most used in the dairy industry; however, studies have suggested the application of emerging technologies, such as ohmic heating (OH), moderate electric fields (MEF), pulsed electric fields (PEF), ultrasound (US), and high hydrostatic pressures (HHP). Most of these processes are non-thermal and could in addition, reduce fermentation time, guarantee or increase the viability of the probiotic, and improve taste and nutritionalquality properties, in addition to increasing shelf life [120]. Subsequently, the milk is cooled (to around 42 to 45 • C) so that starter and probiotic cultures can be added.…”
Section: Aspects Related To the Fermentation Of Probiotic Functional ...mentioning
confidence: 99%
“…During this time, biological activities increase. On the other hand, it was reported that the best results were yielded in an average of 10 days [12]. According to the Food and Drug Administration Model Food Code for Kombucha Brewing, more than 10 days of fermentation are not suggested if produced for human consumption [13].…”
Section: Introductionmentioning
confidence: 99%